Local Particle Traps in the High Latitude Magnetosphere and the Acceleration of Relativistic Electrons - Stepanova, M (2011)
Variations of electron fluxes with energies 300-600. keV in the region of quasitrapping are analyzed using data of the low orbiting Coronas-F satellite. Enhancements in the electron fluxes with energies above 300. keV are observed at the polar boundary of the outer radiation belt. Meteor-3M satellite data, OVATION and AP models of the position of the auroral oval are used to determine the position of analyzed increases in the energetic electrons with respect to the position of the auroral oval. There is a significant number of events when these increases were observed at a few consequent orbits crossing the outer radiation belt boundary. Studied increases in relativistic electron fluxes are localized at the latitudes of the auroral oval. Different mechanisms of formation of observed enhancements are discussed. The possibility of the appearance of increases due to formation of local particle traps is analyzed using Tsyganenko geomagnetic field models. The role of the formation of local particle traps at the boundary of the outer radiation belt and its possible influence to the formation of the outer radiation belt is discussed. © 2010 Elsevier Ltd.